2017
DOI: 10.20961/ijie.v1i2.12472
|View full text |Cite
|
Sign up to set email alerts
|

AR-KIO: Augmented Reality-based Application as Instructional Media on Input and Output Device Component.

Abstract: Abstract:The rapid technology development can be utilized in various fields, especially in education. One of the technologies is augmented reality-based learning media. The learning media can be applied to all the subject matter, including the subject of input and output component devices. Based on the observations that already made, there are some problems such as there is no interactive learning media and limited props in the laboratory. Though the subject of input and output component devices require three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The results showed that the use of technology in the classroom had a positive impact on students perspective on student learning and behavior. Using technology in education tends to make students more independent in learning [5]. Augmented reality makes the process of visualization and delivery of information more varied where information can be presented using digital media, one of which is a 3-dimensional object [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the use of technology in the classroom had a positive impact on students perspective on student learning and behavior. Using technology in education tends to make students more independent in learning [5]. Augmented reality makes the process of visualization and delivery of information more varied where information can be presented using digital media, one of which is a 3-dimensional object [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian perancangan sistem rancang bangun pembersih tangan otomatis, meliputi pembuatan pembersih tangan automatis yang bekerja menyesuaikan dengan wadah [3], menggunakan mikrokontroler pada penghitungan suatu posisi tertentu bagi sensor dan telapak tangan diposisikan kearah mata sensor lalu meletakanya dan memakai kemampuan waktu dibawahnya [4], Penggunaan ATmega328P untuk membuat pembersih tangan pintar [5], membuat pembersih tangan dan pengering otomatis [6].…”
unclassified